2017
DOI: 10.1002/prot.25247
|View full text |Cite
|
Sign up to set email alerts
|

Different dynamics and pathway of disulfide bonds reduction of two human defensins, a molecular dynamics simulation study

Abstract: Human defensins are a class of antimicrobial peptides that are crucial components of the innate immune system. Both human α defensin type 5 (HD5) and human β defensin type 3 (hBD-3) have 6 cysteine residues which form 3 pairs of disulfide bonds in oxidizing condition. Disulfide bond linking is important to the protein structure stabilization, and the disulfide bond linking and breaking order have been shown to influence protein function. In this project, microsecond long molecular dynamics simulations were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
(58 reference statements)
2
27
0
Order By: Relevance
“…Novel discoveries have been made with regard to the structure, functional diversity, and effect on host microbiota of these peptides (Sugi et al, 2017; Zhang, 2017). Many of these discoveries point to a much greater role for defensins in host health and immunity than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Novel discoveries have been made with regard to the structure, functional diversity, and effect on host microbiota of these peptides (Sugi et al, 2017; Zhang, 2017). Many of these discoveries point to a much greater role for defensins in host health and immunity than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting structural feature of HBD1, according to NMR data, is the lack of strong and well-defined interactions between secondary structure elements [ 44 ]. Also, deuterium exchange does not indicate the presence of extensive hydrogen bonding between the β-strands [ 45 ]. Also, common structural feature among defensins is their lack of hydrophobic cores and lack of extensive hydrogen bonding, implying conformation plasticity, an important characteristic for biological functions involving differing targets.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The structure is stabilized primarily by disulfide bonds, allowing it to tolerate extensive residue substitution without disturbing the final tertiary structure. Molecular dynamics simulations performed by Zhang et al revealed microsecond-long motions in α-defensin 5 and β-defensin 3 [ 45 ]. As also shown by their NMR results, despite the presence of disulfide bonds, these defensins present dynamic properties.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Covalent bonding between identical proteins can fulfill numerous purposes depending on the flexibility of the linker. The unstructured highly flexible linker of a Lys-ε-amide bond in ubiquitylation [1,2] allows for the free rotation of the linked domains, while the highly ordered contact surface in dimeric defensin covalently fixed by three intermolecular disulfide bonds prevents any independent mobility of either domain [3]. In both cases, the structural integrity and the resulting dynamics can exert a decisive influence on the biological functions of the proteins [4,5].…”
Section: Introductionmentioning
confidence: 99%